2017
DOI: 10.1093/annonc/mdw616
|View full text |Cite
|
Sign up to set email alerts
|

MRI assessment and outcomes in patients receiving neoadjuvant chemotherapy only for primary rectal cancer: long-term results from the GEMCAD 0801 trial

Abstract: mrEMVI is an independent prognostic factor at baseline for poor outcomes in rectal cancer treated with neoadjuvant chemotherapy while ≤ypT3a is associated with an improvement in DFS. Future preoperative therapy evaluation in rectal cancer patients will need to stratify treatment according to baseline EMVI status as a crucial risk factor for recurrence in patients with predicted CRM clear rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 19 publications
1
69
0
2
Order By: Relevance
“…In the present study, mrEMVI at baseline was a strong predictor of DFS. This is concordant with previous studies that found mrEMVI to be associated with poor prognosis. In a large meta‐analysis including 1262 patients, those with mrEMVI developed metastases more frequently than those with mrEMVI‐negative tumours (odds ratio 5·68; P < 0·001).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, mrEMVI at baseline was a strong predictor of DFS. This is concordant with previous studies that found mrEMVI to be associated with poor prognosis. In a large meta‐analysis including 1262 patients, those with mrEMVI developed metastases more frequently than those with mrEMVI‐negative tumours (odds ratio 5·68; P < 0·001).…”
Section: Discussionsupporting
confidence: 90%
“…The mrTRG was also evaluated to determine the degree of tumour replacement by fibrotic or mucinous changes. Favourable mrTRG was defined as grades 1 and 2, and unfavourable mrTRG as grades 3, 4 and 5.…”
Section: Methodsmentioning
confidence: 99%
“…This evaluation can be performed within days to weeks of the start of the intervention and prior to surgery by assessing volume effects using RECIST criteria with CT or MRI [4,5], MRI based tumour regression grading [6], and mapping macroscopic and microscopic details about tumour architecture [7,8]. Results of prospective trials showed clinical complete response (cCR) or TNM down-staging after CRT is a biomarker of more favourable oncological outcomes in LARC [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the European Society for Medical Oncology guidelines suggest that mrEMVI indicates high risk; CRT followed by TME is recommended in such cases [24]. Moreover, several studies have shown that the presence of ymrEMVI, which was evaluated after the neoadjuvant treatment, and not only mrEMVI, had prognostic impact [23,[25][26][27]. Our study revealed that mrEMVI remained after NAC except for 2 patients.…”
Section: Discussionmentioning
confidence: 58%